COMPARISON OF FINANCIAL LITERACY LEVELS OF FACULTY OF ECONOMICS AND BUSINESS (FEB) AND NON-FEB STUDENTS BASED ON FINANCIAL BEHAVIOR - Suyono, Aji Prasetyo; Mukhsin, Muhammad; Kinanti , Kartika Ayu (Fakultas Ekonomi dan Bisnis, Universitas Teknologi Sumbawa, 2025)
This study aims to compare the level of financial literacy between students from the Faculty of Economics and Business (FEB) and students from other faculties (non-FEB). This comparison will be conducted using indicators of financial behavior demonstrated by students. This research is a quantitative study using the comparative descriptive method. Conclusions are drawn from data processing based on percentage analysis and trend analysis. The sample of students in this study were students from the Faculty of Economics and Business (FEB) and non-FEB students from various state and private universities in Surabaya, Jember, Malang, Semarang, and Lumajang. Both students from the Faculty of Economics and Business (FEB) and non-FEB students have high levels of financial literacy. These results contradict the assumption that students from the Faculty of Economics and Business (FEB) have better financial literacy than students from other faculties (non-FEB). This research is expected to enrich the literature on financial literacy, particularly by comparing two groups of students (FEB and non-FEB) with different educational backgrounds and exposure to information. The results are expected to bridge the gap between multidisciplinary disciplines, namely economics/finance and social/behavioral sciences.